Role and practical guidelines for the use of radiotherapy in neuroblastoma — a narrative review of literature and clinical trial protocols - Aleksandra Jadwiga Sztuder; Marek Ussowicz; Agata Szulc; Beranarda Kazanowska; Adam Jozef Maciejczyk (Reports of Practical Oncology and Radiotherapy)
Neuroblastoma is the most common extracranial solid tumor in children, requiring multidisciplinary treatment, including radiotherapy, which is primarily applied in the high-risk group to prevent disease progression. The review highlights indications for radiotherapy, its role in multimodal treatment, and addresses aspects of radiotherapy planning, including target volume definition, prescribed radiation doses, optimal timing for radiotherapy implementation, and potential side effects. Particular attention is drawn to the lack of consensus regarding the necessity of an additional radiation dose for persistent residual disease in the primary tumor and the irradiation of metastatic sites remaining after induction therapy. To conclude, monitoring quality assurance in radiotherapy planning and delivering processes based on unified standards appears to be crucial.